Modern Criticism and Theory / A Reader - Lodge David (Longman, 1993)
A selection of important and representative work from all the major theoretical schools or tendencies in contemporary criticism. Foreword, Acknowledgements, Contents Arranged Historically, Contents Arranged Thematically, Formalist and structuralist and Post-Structuralist Poetics and Linguistics and Narratology, Deconstruction, Psychoanalysis, Politics and Ideology and Cultural History, Feminism, Hermeneutics and Reception Theory and Reader-Response, Cognitive Literacy Scholarship, Index.